Meanings of family under the perspective of parents of adolescent students - Francisca Georgina Macedo de Sousa; Leda Barros de Castro; Ana Larissa Araujo Nogueria; Italo Rodolfo Silva; Dennyse Cristina Macedo da Silva; Nayra Michele Anjos Amorim (Universidade Federal do Ceará, 2014)
This study aimed to understand the meanings of family according to parents of adolescent students. A qualitative research conducted with nine parents of adolescents from a public school, Maranhão, Brazil. Data collection occurred through unstructured interview from February to April 2011, and were submitted to thematic content analysis. Eight themes emerged: Structure, values and meanings of family; Roles and functions of family members; Family and school; Family dynamics and the health-disease process in the family; Affective bonds and family relationships; Strategies for family functioning; Feelings and support network; Adolescence and the adolescent in the family. The meanings of family overtook consanguinity, extending to friendship, solidarity and affection in a dynamic relationship that involves dialogue, affection, love and responsibility.